Patterned gene expression directs bipolar planar polarity in Drosophila. - Zallen, J.A.; Wieschaus, E. (Developmental Cell, 2004)
During convergent extension in Drosophila, polarized cell movements cause the germband to narrow along the dorsal-ventral (D-V) axis and more than double in length along the anterior-posterior (A-P) axis. This tissue remodeling requires the correct patterning of gene expression along the A-P axis, perpendicular to the direction of cell movement. Here, we demonstrate that A-P patterning information results in the polarized localization of cortical proteins in intercalating cells. In particular, cell fate differences conferred by striped expression of the even-skipped and runt pair-rule genes are both necessary and sufficient to orient planar polarity. This polarity consists of an enrichment of nonmuscle myosin II at A-P cell borders and Bazooka/PAR-3 protein at the reciprocal D-V cell borders. Moreover, bazooka mutants are defective for germband extension. These results indicate that spatial patterns of gene expression coordinate planar polarity across a multicellular population through the localized distribution of proteins required for cell movement.